2019
DOI: 10.1038/s41420-019-0211-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-independent and -dependent p53-mediated apoptosis in response to genotoxic and non-genotoxic stress

Abstract: We previously reported that p53-mediated apoptosis is determined by severity of DNA damage, not by the level of p53, in doxorubicin-treated prostate cancer cells. In addition to doxorubicin, our results here indicated that camptothecin and bortezomib, which are a topoisomerase 1 poison and a 26 S proteasome inhibitor, respectively, could also induce apoptosis in a p53-dependent manner in prostate cancer. Then, we examined whether p53-mediated apoptosis induced by genotoxic and non-genotoxic stress occur in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The p53 family proteins, including p53, p63 and p73 [1][2][3][4][5][6], share a functional and molecular interconnection in the cascade of events triggered by the DNA damage response [7][8][9][10][11][12]: genotoxicity triggers activation of these transcriptional factors leading to activation of a shared transcriptional signature, including p21, Bax, PUMA and NOXA, which is responsible for the p53 family effects on cell cycle progression and apoptosis [11,[13][14][15][16][17]. However, while the best characterized family member, p53, plays major role in tumor suppression [18][19][20][21][22][23][24][25][26][27], the homologue p73, also exerts fundamental independent functions [3,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The p53 family proteins, including p53, p63 and p73 [1][2][3][4][5][6], share a functional and molecular interconnection in the cascade of events triggered by the DNA damage response [7][8][9][10][11][12]: genotoxicity triggers activation of these transcriptional factors leading to activation of a shared transcriptional signature, including p21, Bax, PUMA and NOXA, which is responsible for the p53 family effects on cell cycle progression and apoptosis [11,[13][14][15][16][17]. However, while the best characterized family member, p53, plays major role in tumor suppression [18][19][20][21][22][23][24][25][26][27], the homologue p73, also exerts fundamental independent functions [3,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, p21 has been reported as a key molecule, which plays an important role in regulation of the critical G1 to S phase transition of the cell cycle, senescence and apoptosis, and to be positively regulated by p16 [ 16 ]. Moreover, previous studies demonstrated that p21 could be up-regulated and resulted in cell cycle arrest at G1 phase in a p53-independent manner [ 17 , 18 , 36 ]. In addition, it had been also revealed that paclitaxel could induce the cell apoptosis with a p53-independent way [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the cell cycle is regulated by Cyclin-Dependent Kinases (CDKs), which are activated at specific points during progression of the cell cycle. Arresting the cell cycle at any phase of G1, S, and G2/M of the cell cycle inhibits cell division and may ultimately cause cell death [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…p53, p63 and p73 define the p53 family of transcription factors. All three are transcribed as several distinct protein isoforms [ 37 40 ]. Two alternative promoters drive the expression of either a transcriptionally active p73 (TA isoforms) proteins [ 41 ], containing a full N-terminal transactivation domain (TAD), or a N-terminally truncated (ΔN isoforms) proteins [ 42 ], that lack the TAD.…”
Section: The Case Of Neuroblastomamentioning
confidence: 99%